The Labour Market Impact of Immigration: Quasi-Experimental Evidence - Albrecht Glitz (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2006)
With the fall of the Berlin Wall, ethnic Germans living in the former Soviet Union and the Warsaw Pact countries were given the chance to migrate to Germany. Within 15 years, 2.8 million individuals moved. Upon arrival, these immigrants were exogenously allocated to different regions by the administration in order to ensure an even distribution across the country. Their inflows can therefore be seen as a natural experiment of immigration, avoiding the typical endogeneity problem of immigrant inflows with regard to local labour market conditions. I analyse the effect of these exogenous inflows on relative skill-specific employment and wage rates of the resident population in different geographical areas between 1996 and 2001. The variation I exploit in the empirical estimations arises primarily from differences in the initial skill composition across regions. Skill groups are defined either based on occupations or educational attainment. For both skill definitions, my results indicate a displacement effect of around 4 unemployed resident workers for every 10 immigrants that find a job. I do not find evidence of any detrimental effect on relative wages.
Keywords: J21; J31; J61; 330; Immigration; Labour Market Impact; Skill Groups; Germany